Fatigue crack monitoring in train track steel structures using plastic optical fiber sensor. (15th September 2017) - Yang, D; Li, D; Kuang, K S C
Abstract: Plastic optical fiber (POF) sensors have shown excellent potential for damage detection and structural health monitoring in a variety of engineering structures. This paper discusses the feasibility of using POF sensors in conjunction with a signal-processing algorithm capable of detecting and monitoring fatigue-induced cracks in train track steel structures in real time. The POF sensor, which was modified from an existing design to increase the signal sensitivity, allows for accurate detection of a fatigue crack developed in a specimen, and was found to compare well to the reference acoustic emission (AE) sensors and crack opening displacement (COD) gauge attached to the specimen. The crack-detection technique, which relies on capturing the intensity variation of the POF sensor, was not susceptible to any signal fluctuations commonly associated with intensity-based optical fiber sensors. The results show that the technique has potential for use in detecting the initiation and propagation of specific segments of a structure vulnerable to cracking due to external cyclic loading, e.g. at welded joints in train tracks under train loads or offshore structures subject to wave loads. The POF sensor system is composed of inexpensive parts (LED light source, photodetectors, and data acquisition units) and can easily be installed to the host structure. To validate the proposed damage-detection technique, the instrumented specimens are subjected to cyclic loading in order to induce stable crack propagation in the specimen. A COD gauge and AE were used for the purpose of calibration and comparison. The results show remarkable resemblance in terms of crack initiation and propagation identification exhibited by all three types of sensors, highlighting the potential of the proposed sensor for crack initiation detection and subsequent monitoring of crack propagation.